The Role of E-Wom, Brand Image, Brand Experience, and Brand Trust in Shaping Repurchase Intention on Healthy Instant Noodle Products - Puteri, Amanda Safira; Suhud, Usep; Krissanya, Nofriska (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to determine the effect of electronic word of mouth, brand image¸ brand experience, and brand trust on repurchase intention on healthy instant noodle products. The research method used in this research is quantitative method by distributing questionnaires. Sampling using purposive sampling technique by obtaining 341 respondents as samples. The population in this study are consumers of healthy instant noodle products who live in the DKI Jakarta area and have consumed at least one healthy instant noodle product in the last six months. This research was processed using SPSS version 26.0 software and SEM (Structural Equation Model) through AMOS to analyze and generate data from this study. The results of this study indicate that: First, electronic word of mouth, brand image¸ brand experience have a positive and significant influence on brand trust. Second, electronic word of mouth, brand image¸ brand experience, and brand trust have a positive and significant influence on repurchase intention.